2019
DOI: 10.1021/acs.energyfuels.9b02169
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Hydroperoxy Radicals with Primary C1–5 Alcohols: A Profound Effect on Ignition Delay Times

Abstract: Ignition delay times of primary alcohols often display a noticeable sensitivity to their initial reactions with HO 2 radicals. In view of the transient nature of HO 2 radicals, kinetic models on combustion of alcohols utilize theoretically obtained constant parameters for the abstraction HO 2 + alcohols reactions. Rate constants for the title reactions in pertinent kinetic models are often extrapolated from analogous computed values for either alkanes + HO 2 or n-butane + HO 2 reactions. Even for the simplest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
0
18
1
Order By: Relevance
“…Besides the theoretical study from Zhao et al on the decomposition reactions of n -pentanol, Van de Vijver et al explored automatically the reaction kinetics of the six n -pentanol radicals in terms of their potential energy surfaces (PESs) at the UCCSD­(T)-F12a/cc-pVTZ-F12//M06-2 X /6-311++G­(d,p) level of theory and calculated the rate constants for the decomposition and isomerization reactions of n -pentanol radicals on the PESs by solving the master equation. A theoretical investigation on the potential energy surface of low-temperature reactions of n -pentanol has been conducted by Bu et al by employing the G4 compound method, while the rate coefficient for H-abstraction from n -pentanol’s α-site by HO 2 has recently been calculated by Rawadieh et al based on the CBS-QB3 method with transition state theory. Very recently, Duan et al performed ab initio calculations at the CCSD­(T)/aug-cc-pVTZ//M06-2X/cc-pVTZ level on the fate of the 1-hydroxy-1-peroxypentyl radical.…”
Section: Chemical Reaction Modeling and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the theoretical study from Zhao et al on the decomposition reactions of n -pentanol, Van de Vijver et al explored automatically the reaction kinetics of the six n -pentanol radicals in terms of their potential energy surfaces (PESs) at the UCCSD­(T)-F12a/cc-pVTZ-F12//M06-2 X /6-311++G­(d,p) level of theory and calculated the rate constants for the decomposition and isomerization reactions of n -pentanol radicals on the PESs by solving the master equation. A theoretical investigation on the potential energy surface of low-temperature reactions of n -pentanol has been conducted by Bu et al by employing the G4 compound method, while the rate coefficient for H-abstraction from n -pentanol’s α-site by HO 2 has recently been calculated by Rawadieh et al based on the CBS-QB3 method with transition state theory. Very recently, Duan et al performed ab initio calculations at the CCSD­(T)/aug-cc-pVTZ//M06-2X/cc-pVTZ level on the fate of the 1-hydroxy-1-peroxypentyl radical.…”
Section: Chemical Reaction Modeling and Mechanismsmentioning
confidence: 99%
“…The HO 2 elimination from α-alcohol peroxy radical forming aldehyde and HO 2 has been identified by a set of studies , as the most important alcohol-specific reaction that competes with the low-temperature chain-branching channels and thus inhibits the fuel reactivity at low temperatures significantly. The incorporation of these theoretically derived values into the n -pentanol chemical mechanisms has been shown to improve the model performance successfully. ,, When applying them as rate rules for the analogous reactions of larger alcohols, it is expected that the model prediction uncertainty can be reduced significantly.…”
Section: Chemical Reaction Modeling and Mechanismsmentioning
confidence: 99%
“…Usually, one prefers to use the gold-standard method, i.e., the CCSD­(T)/CBS method, as a benchmarking method, but it is too expensive for the present system as mentioned before. As a compromise, the CBS-QB3 compound method, which has been adopted in predicting kinetic parameters of HO 2 with primary C 1–5 alcohols, was chosen to conduct benchmarking comparison. Specifically, the potential energy calculated at the DLPNO-CCSD­(T)/CBS­(T-Q) level was compared with that at the CBS-QB3 level, for all the target species, noting that the RCs and PCs were not considered for the reactions of HO 2 with 3-pentanol since they will not affect the corresponding rate constants.…”
Section: Resultsmentioning
confidence: 99%
“…The H-abstraction reactions from a fuel molecule by small radicals have been consistently shown to be quite ubiquitous, in dominating the fuel consumption pathway during the combustion process. ,, Considering 3-pentanol, for instance, it is confirmed that H-abstraction reactions through important radicals, such as H, CH 3 , HO 2, and OH, contribute to the majority of fuel consumption flux (≥95%) through reaction pathway analysis, , and the ignition delay times also show high sensitivity to corresponding reactions . Unfortunately, the rate constants of these reactions were obtained either by analogy or estimation rather than experiments or theoretical calculation as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…e relative energies of all stationary points in the vacuum were corrected with zero-point vibrational energies. For all proposed mechanisms, the transition states were analysed using the intrinsic reaction coordinate (IRC) [33][34][35][36][37][38][39], at B3LYP/6-31G(d) and uB3LYP/6-31G(d) levels of theory for nonradical and radical pathways, respectively, to affirm the linkage between the reactant and each of the required intermediate or product. Structures obtained from IRC were optimized to identify the minima to which each transition state is connected.…”
Section: Methodsmentioning
confidence: 99%